Varför väljer små aktiebolag revision sedan avskaffandet av revisionsplikten? : En studie utifrån ett företagsperspektiv - Gidlund, James; Skeppstedt, Carl (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
In 2010, the audit obligation for smaller limited companies was abolished. The change in the law meant that small limited companies could make a choice whether or not they wanted to hire an auditor. Since the abolition, there has been a debate between the politicians and the auditors about the consequences that the abolition has really had. A party that has not been allowed to assert itself in the debate on the abolition of the audit obligation is the companies. The purpose of this study was thus to highlight the companies in this debate and to create an understanding of the reasons why small limited companies choose to hire an auditor and their reasons for dismissing the auditor. Through a qualitative research method, four small limited companies in Luleå were interviewed to investigate their reasons. The study's approach is of a deductive nature where we first chose to investigate what previous research says about companies' reasons for auditing and then compare it with our results. Through this approach, our results indicate that companies have difficulty seeing the benefits of hiring an accountant outweigh the disadvantages. The companies stated the high cost of hiring an auditor in combination with the fact that an auditor does not significantly raise the quality of the annual reports as reasons for refraining from using an auditor. The companies mentioned satisfaction and confirmation as reasons for hiring an auditor and that the authorities are a stakeholder who influences the companies to hire an auditor.